Anaerobic fermentation of organic solid wastes: volatile fatty acid production and separation - TUĞTAŞ KARNABAT, ADİLE EVREN; ÇALLI, BARIŞ; YEŞİL, HATİCE (IWA PUBLISHING, 2014)
Anaerobic fermentation of organic municipal solid waste was investigated using a leach-bed reactor (LBR) to assess the volatile fatty acid (VFA) production efficiency. The leachate recycle rate in the LBR affected the VFA composition of the leachate. A six-fold increase in the recycle rate resulted in an increase of the acetic acid fraction of leachate from 24.7 to 43.0%. The separation of VFAs via leachate replacement resulted in higher total VFA production. VFA separation from synthetic VFA mix and leachate of a fermented organic waste was assessed via a counter-current flow polytetrafluoroethylene (PTFE) membrane contactor. Acetic and propionic acid permeation fluxes of 13.12 and 14.21 g/m(2).h were obtained at low feed pH values when a synthetic VFA mix was used as a feed solution. The highest selectivity was obtained for caproic acid compared to that of other VFAs when synthetic VFA mix or leachate was used as a feed solution. High pH values and the presence of suspended solids in the leachate adversely affected the permeation rate.
Keywords: anaerobic fermentation; leachate; membrane; PTFE; separation; VFAs; PERVAPORATION MEMBRANES; SUCCINIC ACID; RECOVERY; DIGESTION; FRACTION; BROTH